DEVELOPING A NOVEL APPROACH FOR IMPROVING AVAILABILITY OF JOBTRACKER IN HADOOP - Prajakta Mane; Prof. Ravindra J. Mandale (International Journal of Innovations in Engineering Research and Technology, 2021)
Cluster based distributed system containssingles JobTracker and multiple TaskTracker. TaskTracker performs MapReduce operation on DataNode. In this approach, JobTracker facing single point of failure problem. The solution includes theAvatarNode and ZooKeeper. Firstly, AvatarNode uses efficient checkpoint strategy to manage temporary namespace. AvatarNode gives temporary space to store the metadata about current job and flush that data after successful job execution. Secondly, ZooKeeper which is used for session monitoring by communicating with failover manager that is residing in JobTracker andAvatarNode This approach reduces Remote Procedure Call (RPC) traffic between Backup Node and DataNodeby direct communication of JobTracker and AvatarNode.